Molecular phylogeny and taxonomic review of Premnobiini Browne, 1962 (Coleoptera: Curculionidae: Scolytinae) - Cognato, Anthony I. (Frontiers in Ecology and Evolution, 2013)
The taxonomy of Premnobiini is reviewed in the context of a molecular phylogeny including species of Ipini, Dryocoeotini, and Xyleborini. DNA data from COI, 16S, 28S, and CAD ( 2640 characters) were generated for 79 species. Parsimony and Bayesian methods, using multiple sequence alignment methods and partitioning regimes, were used to reconstruct the phylogeny. The resulting topologies are generally congruent. Ipini is monophyletic along with all genera except Acathotomicus. Premnobiini is nested within Ipini and consists of two clades, which associate with the type species of Premnobius and Premnophilus, and with morphological diagnostic characters. The following taxonomic changes are made based on the recovered relationships. Premnophilus is resurrected as a valid genus and Premnobiini is considered a sub-tribe of Ipini.